TUMBUH KEMBANG ANAK PADA IBU YANG BEKERJA - Ummi Masrufah Maulidiyah; andini dwi arumsari (Universitas Narotama, 2022)
Working mothers have a dual role apart from being career women as well as housewives. One of the negative impacts of working mothers is not being able to give full attention to their children when children are in a stage of rapid growth and development. Even though mothers have an important role in raising children. Therefore proper parenting is needed so that children can grow and develop optimally. The purpose of this study is to describe how the growth and development of children in working mothers. This research is a descriptive research that comes from journal and article references and other sources obtained from books. The results of this study are that working mothers have a dual role apart from being career women as well as housewives. One of the negative impacts of working mothers is not being able to give full attention to their children when children are in a stage of rapid growth and development. Even though mothers have an important role in raising children. Therefore proper parenting is needed so that children can grow and develop optimally. For example, by spending time on working days off studying and playing with children, taking time every day during work breaks to communicate with children through babysitters or parents who look after children via telephone or WhatsApp video calls. Accompanying children after returning from work by repeating lessons or playing together so that the role of working mothers can know the growth and development of children properly. Keywords: growth and development, child, working mother